(untitled) (International Journal of Ayurveda and Pharma Research, 2017)
Cerebral palsy is a non-progressive but crippling neurological disorder in children. The prevalence rate of cerebral palsy has risen to well above two per thousand life birth. Spastic cerebral palsy is a disorder that causes muscle tightness. This condition prevents the normal development of motor function. It makes up over 70% of all cases of cerebral palsy. As per Ayurvedic classics, the spasticity is termed as Jadatwam and is one of the Vatha predominant Lakshana. The important causative factors are the improper diet and regimen followed during pregnancy, Akalapravahanam (untimely contractures during labour), head injury during delivery, Garbha sosham (Intrauterine Growth Retardation) etc. Due to these aetiology Dhadhu, Kshaya occurs followed by Vata dosha prakopa and produces symptoms like Praseka, Sosha, Jadatwam etc. In this study, based on the concept of Vathavyadhi chikitsa, Snehana, Swedana, Sodhana and Brimhana therapy with appropriate Panchkarma procedure was done. Physiotherapy was provided along with treatment, it helped to improve motor functions and activities of daily living of the patient. The spasticity was assessed through the range of motion of joints (ROM) by using the instrument Goniometer while the motor and mental developments were assessed by developmental assessment scales for Indian infants (DASII). Considering the ROM of joints of upper and lower limb, spasticity was reduced in the extension movement of the ankle, hip, knee, elbow, and shoulder. The motor and mental developmental quotient of the baby was improved after the treatment. This article is an attempt to highlight the efficacy of conventional Ayurvedic management in spastic cerebral palsy with Kerala specialties.